Hyperpigmented Patch With Linear Extension. Issue 2 (March 2020) - Sable, Kimberly A.; Lake, Eden
Abstract : ABSTRACT: This is the case of a 29-year-old man with a well-demarcated, irregularly shaped, hyperpigmented patch located on the dorsal left hand with linear extension spreading across the distal medial surface. The patch initially presented as an erythematous lesion accompanied by burning, which subsided. A multiple-choice clinical question addressing the underlying diagnosis is offered. An answer is provided with a follow-up discussion focusing on underlying pathology, typical clinical presentation, and suggested management guidelines.